JEP 2019
DOI: 10.7176/jep/10-12-13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Parental Involvement on Academic Performance of Students

Abstract: The present study was undertaken to examine the relationship between parental involvement and academic performance of students at higher secondary classes. Two research questions and two hypotheses were developed. For this study sequential explanatory mixed method design was used. Population was students of higher secondary classes studying in Karachi. Quota sampling was used because population was comprised three group of students including arts, commerce and science. Two hundred students of higher secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 7 publications
1
3
1
Order By: Relevance
“…This finding corroborates the view of Fuudia (2019) who avers that active engagement of parents in the day-to-day activities of their children outside the school enhances the academic achievement of only the children who have high level of academic effort. However, the finding is incongruent with the submissions of Hanif and Alwi (2019), Lara andSaracostti (2019), andOtero et al (2021) who all indicated a direct influence of parental involvement on academic achievement of pupils.…”
Section: Discussioncontrasting
confidence: 64%
See 4 more Smart Citations
“…This finding corroborates the view of Fuudia (2019) who avers that active engagement of parents in the day-to-day activities of their children outside the school enhances the academic achievement of only the children who have high level of academic effort. However, the finding is incongruent with the submissions of Hanif and Alwi (2019), Lara andSaracostti (2019), andOtero et al (2021) who all indicated a direct influence of parental involvement on academic achievement of pupils.…”
Section: Discussioncontrasting
confidence: 64%
“…The work schedule, resources and negative attitudes of parents makes it difficult for them to get involved in their children's education as expected. The views of Chowa et al are consistent with that of Hanif and Alwi (2019) who posit that parental involvement is much less influential on the academic performance of students.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations